Artificial Helical Screws of 2D Materials with Archimedean Spiral Arrangement. (5th February 2023) - Hwang, Ho Seong; Jung, Hong Ju; Kim, Jin Goo; Jeong, Hyeon Su; Lee, Won Jun; Kim, Sang Ouk
Abstract: Helix structures, which are frequently observed in nature, act as versatile structural templates for complex functionalities with asymmetry and anisotropy. However, atomically thin 2D materials, including graphene, transition metal dichalcogenides (TMDs), and MXenes, do not have inherent chirality in their planar geometry and cannot easily form such a structure. This study presents the macroscopic self‐assembly of 2D materials for helical screws with an Archimedean spiral arrangement. The naturally triggered spontaneous rotation upon the 1D fiber assembly of 2D materials forms helical screws consisting of multiple helices and perversions. For a clear understanding of the morphological evolution of helical screws, variations in the helical pitch and angle are systematically analyzed considering thermodynamic and kinetic conditions. Subsequently, the influence of spontaneous helix formation on the properties of the 2D assembled fibers is investigated in terms of the solvent‐driven actuator performance and electrical and electrothermal properties. The suggested approach provides a new perspective on the directed self‐assembly of inherently achiral 2D materials toward chiral helix formation. Abstract : 2D material‐based helical screws with an Archimedean spiral arrangement are naturally assembled via spontaneous rotation generated from anisotropic internal stress. Thermodynamic and kinetic control influence the resultant morphology of helical screws by manipulating the pitch and helical angle. Helix formation induces unique properties in helical screws, including solvent‐driven actuator performance and electrical and electrothermal properties.